Location of Radiosensitive Organs, Measurement of Absorbed Dose to Radiosensitive Organs and Use of Bismuth Shields in Paediatric Anthropomorphic Phantoms - Inkoom, S. (University of Ghana, 2014)
The aim of this study was in two to investigate; firstly, (i) location of radiosensitive organs in the interior of four (4) paediatric anthropomorphic phantoms, and, secondly, (ii) effectiveness of single and double bismuth thyroid shields, distance between shield and phantom surface, during paediatric multi-detector computed tomography (MDCT) using fixed tube current (FTC) and automatic exposure control (AEC) on dose reduction and image quality. Four (4) paediatric anthropomorphic phantoms representing the equivalent of a newborn, 1-, 5-, and 10-y-old child underwent head, thorax and abdomen computed tomography (CT) scans. CT and magnetic resonance imaging scans of all children aged 0-16 y-old performed during a 5-y-period at the University Hospital of Heraklion, Crete, Greece were reviewed, and five hundred and three (503) were found to be eligible for normal anatomy. Anterior-posterior and lateral dimensions of twelve (12) of the above children closely matched that of the phantoms‟ head, thoracic and abdominal region in each four (4) phantoms. The mid-sagittal plane (MSP) and mid-coronal plane (MCP) were drawn on selected matching axial images of patients and phantoms. Multiple points outlining large radiosensitive organs and centres of small organs in patient images were identified at each slice level and their orthogonal distances from the MSP and MCP were measured. The outlines and centres of all radiosensitive organs were reproduced using the coordinates of each organ on the corresponding phantoms‟ transverse images. The four (4) phantoms were also subjected to routine head and neck, neck and thorax CT scans on a 16-slice CT system. Each phantom was first scanned with both FTC and AEC for with and without bismuth shields. Each scan was repeated ten (10) times to increase thermoluminescent dosimeters (TLDs) signal and reduce measurement statistical error. For neck CT, the effect of using single and double thickness of bismuth shields and 1-3 cm cotton spacers placed between the phantom surface and the shield on thyroid dose reduction and image quality was studied. Dose measurements were performed for each scan type using TLDs placed at internal locations in the phantoms and on the phantoms‟ surface. The thyroid organ and surface dose, eye lenses and breast surface dose were estimated separately. Anthropometric data of patients matching with the phantoms was used to locate each organ in the phantom slices. Effective dose was estimated by the dose-length product (DLP) method using specific normalised effective dose per DLP conversion factors for head, neck and thorax, by International Commission on Radiological Protection 103 recommendations. The location of the following radiosensitive organs in the interior of the four (4) phantoms was determined: brain, eye lenses, salivary glands, thyroid, lungs, heart, thymus, esophagus, breasts, adrenals, liver, spleen, kidneys, stomach, gall bladder, small bowel, pancreas, colon, ovaries, bladder, prostate, uterus and rectum. For head and neck CT scans, a maximum dose reduction of 44% / 34% (10-y-old) was achieved for thyroid surface / organ dose by FTC scanning. The use of AEC reduced the thyroid surface / organ dose compared with FTC to a maximum of 61% / 54% (5-y-old). The combined use of shield and AEC further reduced the thyroid surface / organ dose to a maximum of 79% / 68% (10-y-old). The 10-y-old phantom received the highest dose to the eye lenses (38.6 mGy) from head and neck CT for FTC, whilst 27.6 mGy was achieved for AEC scans. For neck CT scans, the use of single bismuth shield during FTC scanning reduced the thyroid surface dose to a maximum of 46% (5-y-old); whilst the thyroid organ dose was reduced to 35% (10-y-old). The use of double shields further reduced the surface dose to a maximum of 57% (5-y-old); whilst the thyroid organ dose was reduced to 47% (10-y-old). The activation of AEC reduced the thyroid surface dose to a maximum of 50% (5-y-old), whilst the thyroid organ dose was reduced to 46% (10-y-old). The combined use of single shield and AEC reduced the thyroid surface dose to a maximum of 70% (5-y-old); whilst the thyroid organ dose was reduced to 62% (10-y-old). The use of double shields and AEC activation further reduced the surface / organ dose to 76% / 65% (5-y-old). The maximum dose to the eye lenses due to neck CT was 7.0 mGy / 6.2 mGy (10-y-old) for FTC / AEC. The maximum breast dose attributable to neck CT was 0.6 mGy for 5-, and 10-y-old phantoms for all protocols. For thorax CT scans, the use of AEC induced a significant increase in the thyroid organ dose by a maximum value of 70% (1-y-old), and thyroid surface dose by 70% (newborn), and mean breast surface dose by 69% (newborn). The maximum increase of the effective dose as a result of application of AEC was 54% (newborn). In conclusion, the production of charts of radiosensitive organs inside paediatric anthropomorphic phantoms for dosimetric purposes was feasible. In-plane bismuth thyroid shielding decreases radiation dose in MDCT with/without deteriorating image quality. AEC was more effective in thyroid dose reduction than in-plane bismuth shields (head and neck CT, neck CT). AEC increased the absorbed dose to both the thyroid and the breast, as well as the effective dose in thorax CT. Thus, AEC should be abandoned as a dose optimisation tool during thoracic MDCT, especially in neonates, infants and children younger than 10-years-old. Placement of the spacer between shield and surface had no significant impact on the measured doses, but significantly decreased the image noise.
Thesis(PHD)-University of Ghana, 2014
Keywords: Radiosensitive Organs; Absorbed Dose; Radiosensitive Organs; Bismuth Shields